GERHANA DALAM PERSPEKTIF HUKUM ISLAM DAN ASTRONOMI - Zaman, Qomaruz (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2016)
From al-Mughirah son of Shu'bah r.a. (Narrated that) he said: There was a solar eclipse on the day of the death of Ibrahim. Then there are those who say the eclipse was due to the death of Ibrahim. Then the Messenger of Allah said: Verily the sun and moon are two of the signs of Allah. The two do not eclipse because of the death or life of a person. When you see it, then pray and pray to God. (Bukhari).In general, the phenomenon of the eclipse is a celestial event casting shadows all other heavenly bodies, which at times when the shadow of the object is to cover the entire disk of the sun, so that the celestial bodies fall of the shadow of other celestial bodies, it can not receive sunlight at all. Kata Kunci: Salat Gerhana, Gerhana Bulan, Gerhana Matahari